2020
DOI: 10.1002/ange.202004892
|View full text |Cite
|
Sign up to set email alerts
|

Holey Lamellar High‐Entropy Oxide as an Ultra‐High‐Activity Heterogeneous Catalyst for Solvent‐free Aerobic Oxidation of Benzyl Alcohol

Abstract: The development of noble-metal-free heterogeneous catalysts is promising for selective oxidation of aromatic alcohols;h owever,t he relatively lowc onversion of non-noble metal catalysts under solvent-free atmospheric conditions hinders their industrial application. Now,aholey lamellar high entropyoxide (HEO) Co 0.2 Ni 0.2 Cu 0.2 Mg 0.2 Zn 0.2 Omaterial with mesoporous structure is prepared by an anchoring and merging process.The HEO has ultra-high catalytic activity for the solvent-free aerobic oxidation of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“….). 22,[32][33][34][35][36][37][38] Very recently, it has been demonstrated that high entropy oxides (HEOs) in the form of nanofibers (NFs) can be successfully prepared by the electrospinning technique. [39][40][41][42][43] Zhao et al 39 have reported the synthesis of electrospun high entropy (La 1/5 Sm 1/5 Eu 1/5 Gd 1/5 Tm 1/5 ) 2 Zr 2 O 7 NFs with excellent thermal…”
Section: Introductionmentioning
confidence: 99%
“….). 22,[32][33][34][35][36][37][38] Very recently, it has been demonstrated that high entropy oxides (HEOs) in the form of nanofibers (NFs) can be successfully prepared by the electrospinning technique. [39][40][41][42][43] Zhao et al 39 have reported the synthesis of electrospun high entropy (La 1/5 Sm 1/5 Eu 1/5 Gd 1/5 Tm 1/5 ) 2 Zr 2 O 7 NFs with excellent thermal…”
Section: Introductionmentioning
confidence: 99%
“…Entropy-stabilized materials (ESMs) represent a recently emerged fascinating research field, gathering huge scientific attention. ESMs, also known as high-entropy materials (HEMs), consist in multicomponent solid solutions containing at least five cations Feng et al [22] have shown "ultra-high" catalytic activity of holey lamellar (Mg, Co, Ni, Cu, Zn) ESO with the mesoporous structure for the solvent-free aerobic oxidation of benzyl alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…Long-range ordering can be minimized by mixing isostructural components or elements having a similar charge. [5] The ESM family includes alloys, [1,2] oxides, [9] and other composites, [10][11][12][13][14][15] which exhibit a variety of structures (rock-salt, spinel, perovskite, fluorite…) and are endowed with enhanced properties that make them very promising candidates for a very wide range of applications, spanning from catalysis [16][17][18][19][20][21][22][23][24] to energy conversion and storage. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] Rock-salt (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O was the first singlephase multicomponent oxide successfully synthesized, in 2015, via solid-state reaction from an equimolar mixture of MgO, CoO, NiO, CuO, and ZnO.…”
mentioning
confidence: 99%
“…Consequently, there is a current scientific effort concerning the development of a selective heterogeneous catalyst for this process using clean oxidants. In this sense, various systems such as hydrotalcites, 6 heteropoly-acids 7 or mixed metal oxides 8,9 capable of performing selective alcohol dehydrogenation have been proven to have enough chemical and thermal stability. However, considering reactants’ accessibility to active sites and metal leaching from solid supports, the most relevant materials designed up to now are metal nanoparticles such as Co, Ir, Pt, Pd or Au supported on different materials (metal oxides or carbon).…”
Section: Introductionmentioning
confidence: 99%